Formulasi Sediaan Krim Tabir Surya dari Ekstrak Etanol Buah Bisbul (Diospyros blancoi) - Harry Noviardi; Devi Ratnasari; Muhammad Fermadianto (JURNAL ILMU KEFARMASIAN INDONESIA, 2019)
Bisbul fruit is one of the tropical plants that grows in Indonesia. Phytochemical contents of bisbul fruit are alkaloids, tannins, flavonoids and phenolic compounds. Flavonoids and phenolic compounds are potentially as antioxidants. Antioxidants could inhibit skin cell damage due to oxidation process. This study aimed to make the optimum sunscreen cream, based on quality, stability and activity as a sunscreen from bisbul fruit (Diospyros blancoi). The sample used in this research was bisbul, which made into extract. The extraction was done by a maceration method using 95% ethanol solvent. The results showed that extract yield obtained was 12%. Furthermore, made into a sunscreen cream preparation with concentrations of 10, 20, and 40%. The cream had been made, then was evaluated the quality organoleptic test, pH, adhesiveness, dispersive power, viscosity, stability, and the Sun Protection Factor (SPF) value. The results showed that of bisbul extract could be made into a sunscreen cream. The SPF value obtained from the extract concentration of 10, 20, and 40% consecutively were 9.25; 10.02; and 13.00. Furthermore, it could be concluded that the formula with a concentration of 40% was the best quality of the cream and the highest SPF value of 13.00 with maximum protection.